2016
DOI: 10.1128/mcb.00800-15
|View full text |Cite
|
Sign up to set email alerts
|

Lrp5 Has a Wnt-Independent Role in Glucose Uptake and Growth for Mammary Epithelial Cells

Abstract: Lrp5 is typically described as a Wnt signaling receptor, albeit a less effective Wnt signaling receptor than the better-studied sister isoform, Lrp6. Here we show that Lrp5 is only a minor player in the response to Wnt3a-type ligands in mammary epithelial cells; instead, Lrp5 is required for glucose uptake, and glucose uptake regulates the growth rate of mammary epithelial cells in culture. Thus, a loss of Lrp5 leads to profound growth suppression, whether growth is induced by serum or by specific growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…LRP5 is a closely related paralog of LRP6, but LRP5 is a much less potent transducer of Wnt/b-catenin signaling [MacDonald et al, 2011;Chin et al, 2015]. We found that the level of LRP5 expression is not associated with ER and PR status (Fig.…”
Section: Lrp6 Is Up-regulated In Tnbc Cellsmentioning
confidence: 70%
See 1 more Smart Citation
“…LRP5 is a closely related paralog of LRP6, but LRP5 is a much less potent transducer of Wnt/b-catenin signaling [MacDonald et al, 2011;Chin et al, 2015]. We found that the level of LRP5 expression is not associated with ER and PR status (Fig.…”
Section: Lrp6 Is Up-regulated In Tnbc Cellsmentioning
confidence: 70%
“…Both LRP5 and LRP6 are essential Wnt co‐receptors of the Wnt/β‐catenin signaling pathway [He et al, ]. While LRP5 has a Wnt‐independent role in glucose uptake and growth for mammary epithelial cells [Chin et al, ], LRP6 is a more potent transducer of Wnt/β‐catenin signaling [MacDonald et al, ; Chin et al, ]. Furthermore, LRP5 knockdown induced caspase‐dependent apoptosis in TNBC cells, whereas LRP6 knockdown had no such effect [Maubant et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…A truncated form of LRP5 has been found in more than 80% of breast tumors [ 59 ]. However, like Chin and coworkers [ 49 ], and despite extensive investigations, we were unable to detect this truncated form in tumors or cell lines (unpublished data).…”
Section: Discussionmentioning
confidence: 47%
“…Experiments with LRP5/6 chimeric proteins have revealed that the cytoplasmic regions play a major role in the differences in signaling activity between the coreceptors [ 48 ]. A recent study showed that the depletion of LRP5 impaired the proliferation of mammary epithelial cells, whereas the depletion of LRP6 had no such effect [ 49 ]. The authors found that LRP5 controlled cell growth, not through the Wnt pathway, but through its function in glucose uptake [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The typical sampling length for the grinding surface roughness measurement is 0.8 mm, and usually the evaluation length should contain 5 consecutive sampling lengths. Current methods, however, aim at threedimensional area simulation which is carried out on a rather small scale [1][2][3][4][5]. Much more time will be consumed if the simulation scale is increased.…”
Section: Introductionmentioning
confidence: 99%